DEVELOPMENT OF AN INTERACTIVE SOFTWARE TOOL FOR AUTOMATIC ASSESSMENT AND IMPROVEMENT OF PRONUNCIATION IN FOREIGN LANGUAGE LEARNING - Rohmonqulov , M.E. (Scientific practical conference, 2025)
The development of foreign language skills requires not only vocabulary and grammar knowledge but also accurate pronunciation, which is a critical component of effective communication. However, many learners face challenges in evaluating and improving their pronunciation independently without expert guidance. This paper presents the design and development of an interactive software tool aimed at automatic assessment and enhancement of pronunciation in foreign language learning. The system utilizes speech recognition technologies, phonetic analysis, and artificial intelligence algorithms to provide real-time feedback on learners’ pronunciation accuracy. By offering interactive exercises, performance tracking, and personalized recommendations, the tool creates an engaging learning environment that supports self-directed practice. Experimental analysis and user testing demonstrate that the proposed solution helps learners to identify phonetic errors, monitor progress, and gradually improve their speaking skills. The study highlights the practical significance of integrating automatic pronunciation assessment systems into digital education platforms and suggests directions for further improvements in adaptive language learning technologies.